Geriatric Care Boot Camp: An Interprofessional Education Program for Healthcare Professionals. Issue 5 (May 2015) - Solberg, Lauren B.; Solberg, Laurence M.; Carter, Christy S.
<x xml:space="preserve">Abstract</x> In response to the need for interprofessional geriatrics education, a half‐day geriatric care boot camp for healthcare professionals was held that covered core concepts in geriatric medicine: delirium and dementia, medication management, palliative care, ethics, and a general overview of older adults. Aspects of the curriculum focused on interprofessional education, and the attendees and presenters were healthcare professionals from a wide variety of fields. Primary objectives were to determine changes in knowledge of core concepts in geriatrics and level of comfort in caring for older adults. Secondary objectives assessed whether participants found the interprofessional approach beneficial and whether they used or shared this information with others in their professional activities. Participants completed pre‐ and postassessment surveys. Changes in participant understanding of each core concept were statistically significant, as was the change in comfort level of participants in caring for older adults. Furthermore, attendees found the multidisciplinary perspective of the boot camp beneficial. A 3‐month follow‐up survey assessed whether attendees applied and shared information learned in their own professional activities. Half of the respondents who reported sharing universally shared core concepts. Delirium and dementia information was most frequently shared. Information was most frequently shared with students, nurses, and patients' families. Attendees less frequently shared, or did not share, with physicians, physician assistants, social workers, physical and occupational therapists, nutritionists, and dentists. The healthcare professionals who may benefit greatly from future education programs are those with whom the boot camp information was least frequently shared; thus, they are appropriate targets for advertisements for future programs.